Vegetation dynamics and responses to climate anomalies in East Africa - Musau, John Mwanzia; Patil, Sopan; Sheffield, Justin; Marshall, Michael (My University, 2018)
Vegetation plays a key role in the global climate system via modification of the water and energy balance. Its coupling to climate is therefore important, particularly in the tropics where severe climate change impacts are expected. Consequently, understanding vegetation dynamics and response to present and projected climatic conditions for various land cover types in East Africa is vital. This study provides an assessment of the vegetation trends in East Africa using Leaf Area Index (LAI) time series for the period 1982 to 2011, regression analysis between LAI and Standardised Precipitation Evapotranspiration Index (SPEI), as well as analysis of the temporal non-stationarity in the LAI trends and vegetation response to climate. Our results show mean LAI over the region increased at a rate of about 4×10-3 units per year, while the rate of increase for annual mean temperature was 0.035°C per year. Annual precipitation did not show significant trends. Trend breaks and variations in the stability of LAI time series anomalies significantly alter the LAI trends across the period of study. Drought and wetness conditions also show significant influence on the vegetation dynamics in the region. Given the potential impacts of climate change on vegetation productivity in this region, this study provides the much-needed reference point for the disentanglement of historical climatic- and human-induced vegetation dynamics. In addition, the results indicate key areas of interest for the assessment of potential impacts of vegetation dynamics on land surface water and energy balance in the region.